Trauma a wzorzec objawów impulsywnych u kobiet chorujących na bulimię psychiczną i kompulsywne objadanie się = Trauma to pattern of impulsive symptoms in women suffering from bulimia and compulsive overeating - Izydorczyk, Bernadetta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article was to demonstrate results of the Author's own study that sought relationships between having experienced psychological trauma and the impulsive symptoms in women suffering from bulimia and compulsive overeating . The basic research question was the following: To what degree are the trauma experienced by females with bulimia and symptoms, compulsive overeating related with these females' impulsive symptoms?
Keywords: trauma; objawy impulsywne; bulimia; kompulsywne objadanie się; impulsive symptoms; compulsive overeating